Innovating Videography Instruction in Vocational Schools: A DBR-Based Multimedia Approach - Dita Luthfillah; Asrul Huda; Ika Parma Dewi; Yevgeniya Daineko (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
This study aims to develop and validate an interactive learning medium for the Vocational Videography course at SMK Negeri 2 Padang Panjang using a Design-Based Research (DBR) approach. The media, developed with Adobe Captivate, integrates multimedia elements such as visuals, audio, video tutorials, and interactive quizzes to enhance student engagement and comprehension. The development process followed iterative DBR phases, including problem analysis, prototype design, expert validation, implementation, and reflection. Validation by six experts in educational technology and subject matter resulted in ratings of "valid" to "highly valid" in terms of content quality and instructional design. Practicality testing involving 15 students yielded a score of 85.97%, indicating high usability and acceptance. The findings suggest that the interactive media significantly boosts student motivation and supports competency-based learning in videography education. This research contributes to the advancement of instructional innovation in vocational education by effectively integrating multimedia and offers practical implications for educators aiming to enhance digital learning environments.